Analisis Unsur Matematika pada Bunga Motif Tenun Khas Sumba Barat Kampung Wannorugu Kecamatan Loli - Lango, Ambu Anggreny; Dappa, Olviana; Lede, Yulius Keremata (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to find mathematical aspects contained in the woven cloth motifs of Loli sub-district and their use in mathematics learning. This study was conducted in Dedekadu Village, Loli Sub-district and the subjects were mothers who weave cloth as many as 3 people. This type of research is descriptive qualitative. Data were obtained from the results of interviews with three informants, namely weaving craftsmen. Activities in making woven motifs in the Loli sub-district community include: 1) Designing: designing woven motif patterns, 2) Measuring: measuring the distance using a span for each motif 3) Counting: calculating the number of threads needed. Woven motifs have mathematical aspects such as triangles, squares, rectangles, parallelograms, trapezoids, reflections and translations.